INNOVATIONS IN ISLAMIC FINANCE IN SOUTHEAST ASIA: AN IN-DEPTH REVIEW OF RECENT LITERATURE - Muhammad Syafri; Ahmad Rizani; Abdul Wahab Syakhrani; Eka Sutisna; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
This comprehensive literature review delves into Islamic finance in Southeast Asia, offering a meticulous examination of recent innovations within the industry. Southeast Asia, renowned for its vibrant Islamic finance sector, has witnessed groundbreaking developments that transcend conventional financial paradigms. The abstract embarks on a succinct journey through the review's key facets, encapsulating the essence of the extensive exploration. Against the backdrop of an ever-evolving financial landscape, this review navigates through the recent innovations that have reshaped the contours of Islamic finance. It delves into the burgeoning realm of Shariah-compliant fintech platforms, sustainable and green Sukuk, and innovative microfinance models that empower the underserved. Case studies of successful innovations from Indonesia and Malaysia exemplify the transformative potential of Islamic finance in driving financial inclusion, economic growth, and sustainability. Furthermore, the abstract offers a glimpse into the profound impact of digitalization and fintech on Islamic finance, revolutionizing accessibility, transparency, and efficiency. As Southeast Asia endeavors to become a global hub for Islamic finance, these technological advancements are pivotal in fostering financial inclusion and expanding the industry's reach. This literature review illuminates the dynamic landscape of Islamic finance in Southeast Asia, where innovation converges with ethical principles to shape a promising future. The region's commitment to ethical finance, sustainability, and socioeconomic development makes it a beacon in the ever-evolving world of Islamic finance.